Self-Management and Quality of Life in Diabetic Type II Patients at Mataram University Hospital - Luh Komang Diah Lakhsmi Paramita; Seto Priyambodo; Rifana Cholidah (Universitas Muhammadiyah Yogyakarta, 2023)
Type 2 diabetes mellitus (DM) is the community's most common metabolic disease, indicated by increased blood glucose. Patients with type 2 DM cannot be cured but can be controlled by self-management. Self-management improves the quality of life (QoL) by increasing the quality of metabolic control and reducing the risk of hospitalization and mortality complications of type 2 DM. This study aims to examine the relationship between self-management and the QoL among patients with type 2 DM at the Mataram University Hospital. This study used a cross-sectional analytic method, and the population included outpatients with type 2 DM in Mataram University Hospital. This study employed 40 people selected by the consecutive sampling method and got interviewed to fill out the Diabetes Self-Management Questionnaires (DSMQ) and Asian Diabetes Quality of Life (Asian DQOL) questionnaires. The data analysis used the Spearman statistical test. The majority of the self-management respondents were good (87.5%), and the QoL (95%). The results obtained a p-value of 0.000 (p0.05), indicating a significant relationship between self-management and the QoL of type 2 DM patients in Mataram University Hospital. This result showed that the better the self-management of type 2 DM patients is, the better their QoL will be.